An observational study of feto-maternal outcome in cases of abruptio placentae - Alka, .; Dudhrejia, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abruptio placentae defined as the preterm partial or complete separation of normally situated placenta from the uterine wall, complicating 1 in every 200 pregnancies (0.5-1%) in western nations, with rates as high as 4% in developing nations. Methods: This was a descriptive observational hospital-based study design with a follow-up component conducted over a period of 16 months, from January 2015 to April 2016 in the department of Obstetrics and Gynecology at RZH, PDU Medical College and hospital, Rajkot comprising of 83 cases. Results: A total of 83 cases of abruption placentae were present out of 9102 deliveries at RZH, PDU Medical College, Rajkot between January 2015 to April 2016. The incidence of abruption placentae in our study is 0.9%. Overall global incidence of abruptio placentae ranges between 0.5 to 2 % with more in developing countries as compared to the developed nations. (1a,6a,17a). Fetal adverse outcomes of abruptio placentae observed during study period were perinatal mortality 75.9%, prematurity 71%, low birth weight 69.8% and asphyxia 3.6%. Out of 83 cases, 59 deaths occurred in utero while 4 died in the first week of life. Conclusions: Abruptio placentae is one of the gravest hemorrhagic complications of pregnancy. Incidence in alarmingly high in resource poor set ups of developing countries like ours.The predictors of maternal adverse outcomes were found to be malnutrition, anemia, , PPH, DIC and maternal shock. Predictors for perinatal death were low birth weight, birth asphyxia, low APGAR score, retroplacental clot volume more than 500 ML.